From Economic Boom to Linguistic Bloom: China's Growth and the Global Rise of Mandarin - Joshua Nathanael Hartono (Universitas Negeri Surabaya, 2025)
This research is describing about the phenomenon of China's rapid economic growth that is also strengthening the official Chinese currency (RMB) in worldwide and explores the supporting factor of the rapid growing economics. China is one step away from becoming the world leader surpassing America which has rule the world since 1898. The main findings indicate China’s will to became the next world dominant by focusing on infrastructure, investment, and trade expansion that made Yuan’s position higher every year. The president of China, Xi Jinping launched a Belt and Road initiative which is a global infrastructure development strategy adopted by the government of China in 2013 to invest in more than 150 countries and international organizations The conclusion of this study is that Mandarin is becoming as important as English because of the country economic influence and will be crucial in business communication and diplomacy. China’s ambition is also being supported by the formation of BRICS in 2009 for cooperation among a group of leading emerging economies.